THE IMPACT OF USING TIKTOK MEDIA ON THE CHARACTER OF CARING AND RESPONSIBILITY IN STUDENTS OF THE FACULTY OF SHARIA AND LAW, RADEN FATAH STATE ISLAMIC UNIVERSITY PALEMBANG - Tanjung, Akbar; Abdurrahmansyah, Abdurrahmansyah; Maryamah, Maryamah (Conciencia, 2022)
The purpose of this study was to analyse the use of Tik Tok social media on students of the Faculty of Sharia and Law, Raden Fatah State Islamic University Palembang. To analyse the character of caring and responsibility and to analyse the impact of using Tik Tok social media on character in students of the Faculty of Sharia and Law, Raden Fatah State Islamic University Palembang. This research uses qualitative research methods. Data obtained using interviews, observation and documentation were analysed using data collection, data reduction, data presentation, conclusion drawing. The results of this study indicate that the use of the Tik Tok application at the Faculty of Sharia and Law, Raden Fatah State Islamic University Palembang is quite large, where the users are students. The use of the Tik Tok application as a medium to get entertainment. The impact of using the Tik Tok application on its use on religious behavior is seen from several behaviours, namely: behaviour towards God, Parents, Self, and behaviour towards the community environment where there isnoso negative and significant effects that can change student behaviour. Students still take all actions in accordance with what is taught by parents and religion. Through the Faculty of Shari'ah and Law, Raden Fatah State Islamic University Palembang, it is hoped that it will be able to become a forum for creativity and maintain the behaviour of adolescents from the negative impact of social media.